Whole-Genome and Long-Read Sequencing Identify a Novel Mechanism in RFC1 Resulting in CANVAS Syndrome. (1st December 2022) - King, Katherine Abell; Wegner, Daniel J.; Bucelli, Robert C.; Shapiro, Jessica; Paul, Alexander J.; Dickson, Patricia I.; Wambach, Jennifer A.
Abstract : Objectives: Cerebellar ataxia with neuropathy and bilateral vestibular areflexia syndrome (CANVAS) results from biallelic intronic pentanucleotide repeats in RFC1. We describe an adult male proband with progressive imbalance, cerebellar atrophy, somatosensory neuronopathy, and absence of peripheral vestibular function for whom clinical testing demonstrated a heterozygous RFC1 expansion consistent with an unaffected carrier. Methods: We performed whole-genome sequencing (WGS) on peripheral blood DNA samples from the proband and his unaffected mother. We performed DNA long-read sequencing and synthesized complementary DNA from RNA using peripheral blood from the proband. Results: WGS confirmed the maternally inherited RFC1 expansion and identified a rare, nonsense RFC1 variant: c.C1147T; p.R383X in the proband but not the maternal DNA sample. RFC1 variants were confirmed in trans with long-read sequencing. Functional studies demonstrated the absence of complementary DNA (cDNA) transcript from the c.C1147T; p.R383X variant supporting nonsense-mediated decay of this transcript. Discussion: We report an adult with CANVAS due to compound heterozygous pathogenic RFC1 variants: the pathogenic intronic pentanucleotide expansion confirmed in trans with a nonsense variant. This report represents a novel molecular mechanism for CANVAS. Sequencing for RFC1 should be considered for adults meeting clinical criteria for the CANVAS phenotype if only a heterozygous pathogenic RFC1 expansion is identified.